Answer
Verified
447k+ views
Hint: We have to solve this differentiation using quotient rule. We separately solve for derivatives of numerator and denominator using chain rule and then substitute in the formula for quotient rule. Then separating the terms we try to form trigonometric forms in the final answer.
* Quotient rule states that differentiation of \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right) = \dfrac{{vu' - uv'}}{{{v^2}}}\] where \[u'\]is differentiation of u with respect to x and \[v'\]is differentiation of v with respect to x.
* Chain rule which will be used within the differentiation is given as \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\] where \[f'\]denotes differentiation of function f with respect to x and \[g'\]denotes differentiation of function g with respect to x.
Complete step-by-step answer:
We write the differentiation as \[\dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right)\].
Now comparing with \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right)\], we get \[u = \sin (ax + b),v = \cos (cx + d)\]
First we find the values of \[u'\]and \[v'\]using chain rule.
Since, \[u = \sin (ax + b)\]
\[ \Rightarrow u' = \dfrac{{d(u)}}{{dx}} = \dfrac{d}{{dx}}(\sin (ax + b))\]
According to chain rule \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\]
Substitute the value of \[f(x) = \sin (g(x)),g(x) = (ax + b)\]
Then \[f'(x) = \dfrac{{df(x)}}{{dx}} = \dfrac{{d\sin (g(x))}}{{dx}} = \cos (g(x))\] and \[g'(x) = \dfrac{{dg(x)}}{{dx}} = \dfrac{{d(ax + b)}}{{dx}} = a\]
\[\dfrac{d}{{dx}}\left[ {\sin (ax + b)} \right] = \cos (ax + b).a\]
\[ \Rightarrow u' = a\cos (ax + b)\] … (1)
Since, \[v = \cos (cx + d)\]
\[ \Rightarrow v' = \dfrac{{d(v)}}{{dx}} = \dfrac{d}{{dx}}(\cos (cx + d))\]
According to chain rule \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\]
Substitute the value of \[f(x) = \cos (g(x)),g(x) = (cx + d)\]
Then \[f'(x) = \dfrac{{df(x)}}{{dx}} = \dfrac{{d\cos (g(x))}}{{dx}} = - \sin (g(x))\] and \[g'(x) = \dfrac{{dg(x)}}{{dx}} = \dfrac{{d(cx + d)}}{{dx}} = c\]
\[\dfrac{d}{{dx}}\left[ {\cos (cx + d)} \right] = - \sin (cx + d).c\]
\[ \Rightarrow v' = - c\sin (cx + d)\] … (2)
We solve\[\dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right)\] using quotient rule which is \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right) = \dfrac{{vu' - uv'}}{{{v^2}}}\]
Here, \[u = \sin (ax + b),v = \cos (cx + d)\]and \[u' = a\cos (ax + b),v' = - c\sin (cx + d)\]
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{\left( {\cos (cx + d)} \right)\left( {a\cos (ax + b)} \right) - \left( {\sin (ax + b)} \right)\left( { - c\sin (cx + d)} \right)}}{{{{\left( {\cos (cx + d)} \right)}^2}}}\]
Multiplying the brackets in the numerator
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)\cos (cx + d)} \right) + c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{{{\cos }^2}(cx + d)}}\]
Now we separate the terms in the numerator
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)\cos (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}} + \dfrac{{c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}}\]
Cancelling out the same terms from numerator and denominator.
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)} \right)}}{{\cos (cx + d)}} + \dfrac{{c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}}\]
Now we separate the terms
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = a\cos (ax + b).\dfrac{1}{{\cos (cx + d)}} + c\sin (ax + b).\dfrac{{\sin (cx + d)}}{{\cos (cx + d)}}.\dfrac{1}{{\cos (cx + d)}}\]
Substituting the values of \[\dfrac{1}{{\cos (cx + d)}} = \sec (cx + d),\dfrac{{\sin (cx + d)}}{{\cos (cx + d)}} = \tan (cx + d)\]
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = a\cos (ax + b)\sec (cx + d) + c\sin (ax + b)\tan (cx + d)\sec (cx + d)\]
Thus differentiation of \[\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}\] with respect to x is \[a\cos (ax + b)\sec (cx + d) + c\sin (ax + b)\tan (cx + d)\sec (cx + d)\]
Note: Students are likely to make mistake of multiplying both numerator and denominator by 2 to make use of the formula which will convert the numerator i.e.\[2\sin A\sin B = \cos (A - B) - \cos (A + B)\] and \[2\cos A\cos B = \cos (A + B) + \cos (A - B)\]
Students are advised not to operate in such a way because this makes our angles inside the bracket even more complicated.
* Quotient rule states that differentiation of \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right) = \dfrac{{vu' - uv'}}{{{v^2}}}\] where \[u'\]is differentiation of u with respect to x and \[v'\]is differentiation of v with respect to x.
* Chain rule which will be used within the differentiation is given as \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\] where \[f'\]denotes differentiation of function f with respect to x and \[g'\]denotes differentiation of function g with respect to x.
Complete step-by-step answer:
We write the differentiation as \[\dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right)\].
Now comparing with \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right)\], we get \[u = \sin (ax + b),v = \cos (cx + d)\]
First we find the values of \[u'\]and \[v'\]using chain rule.
Since, \[u = \sin (ax + b)\]
\[ \Rightarrow u' = \dfrac{{d(u)}}{{dx}} = \dfrac{d}{{dx}}(\sin (ax + b))\]
According to chain rule \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\]
Substitute the value of \[f(x) = \sin (g(x)),g(x) = (ax + b)\]
Then \[f'(x) = \dfrac{{df(x)}}{{dx}} = \dfrac{{d\sin (g(x))}}{{dx}} = \cos (g(x))\] and \[g'(x) = \dfrac{{dg(x)}}{{dx}} = \dfrac{{d(ax + b)}}{{dx}} = a\]
\[\dfrac{d}{{dx}}\left[ {\sin (ax + b)} \right] = \cos (ax + b).a\]
\[ \Rightarrow u' = a\cos (ax + b)\] … (1)
Since, \[v = \cos (cx + d)\]
\[ \Rightarrow v' = \dfrac{{d(v)}}{{dx}} = \dfrac{d}{{dx}}(\cos (cx + d))\]
According to chain rule \[\dfrac{d}{{dx}}\left[ {f(g(x))} \right] = f'(g(x)).g'(x)\]
Substitute the value of \[f(x) = \cos (g(x)),g(x) = (cx + d)\]
Then \[f'(x) = \dfrac{{df(x)}}{{dx}} = \dfrac{{d\cos (g(x))}}{{dx}} = - \sin (g(x))\] and \[g'(x) = \dfrac{{dg(x)}}{{dx}} = \dfrac{{d(cx + d)}}{{dx}} = c\]
\[\dfrac{d}{{dx}}\left[ {\cos (cx + d)} \right] = - \sin (cx + d).c\]
\[ \Rightarrow v' = - c\sin (cx + d)\] … (2)
We solve\[\dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right)\] using quotient rule which is \[\dfrac{d}{{dx}}\left( {\dfrac{u}{v}} \right) = \dfrac{{vu' - uv'}}{{{v^2}}}\]
Here, \[u = \sin (ax + b),v = \cos (cx + d)\]and \[u' = a\cos (ax + b),v' = - c\sin (cx + d)\]
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{\left( {\cos (cx + d)} \right)\left( {a\cos (ax + b)} \right) - \left( {\sin (ax + b)} \right)\left( { - c\sin (cx + d)} \right)}}{{{{\left( {\cos (cx + d)} \right)}^2}}}\]
Multiplying the brackets in the numerator
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)\cos (cx + d)} \right) + c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{{{\cos }^2}(cx + d)}}\]
Now we separate the terms in the numerator
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)\cos (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}} + \dfrac{{c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}}\]
Cancelling out the same terms from numerator and denominator.
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = \dfrac{{a\left( {\cos (ax + b)} \right)}}{{\cos (cx + d)}} + \dfrac{{c\left( {\sin (ax + b)\sin (cx + d)} \right)}}{{\cos (cx + d)\cos (cx + d)}}\]
Now we separate the terms
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = a\cos (ax + b).\dfrac{1}{{\cos (cx + d)}} + c\sin (ax + b).\dfrac{{\sin (cx + d)}}{{\cos (cx + d)}}.\dfrac{1}{{\cos (cx + d)}}\]
Substituting the values of \[\dfrac{1}{{\cos (cx + d)}} = \sec (cx + d),\dfrac{{\sin (cx + d)}}{{\cos (cx + d)}} = \tan (cx + d)\]
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}} \right) = a\cos (ax + b)\sec (cx + d) + c\sin (ax + b)\tan (cx + d)\sec (cx + d)\]
Thus differentiation of \[\dfrac{{\sin (ax + b)}}{{\cos (cx + d)}}\] with respect to x is \[a\cos (ax + b)\sec (cx + d) + c\sin (ax + b)\tan (cx + d)\sec (cx + d)\]
Note: Students are likely to make mistake of multiplying both numerator and denominator by 2 to make use of the formula which will convert the numerator i.e.\[2\sin A\sin B = \cos (A - B) - \cos (A + B)\] and \[2\cos A\cos B = \cos (A + B) + \cos (A - B)\]
Students are advised not to operate in such a way because this makes our angles inside the bracket even more complicated.
Recently Updated Pages
How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE
Mark and label the given geoinformation on the outline class 11 social science CBSE
When people say No pun intended what does that mea class 8 english CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Give an account of the Northern Plains of India class 9 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Trending doubts
Which are the Top 10 Largest Countries of the World?
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Give 10 examples for herbs , shrubs , climbers , creepers
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
Why is there a time difference of about 5 hours between class 10 social science CBSE